Circulating hyaluronan as a marker of endothelial glycocalyx damage in dogs with myxomatous mitral valve disease and dogs in a hypercoagulable state. (July 2022) - Lawrence-Mills, Sara J.; Hezzell, Melanie J.; Adamantos, Sophie E.; Chan, Iris; Borgeat, Kieran; Rose Payne, Jessie; Satchell, Simon; Welsh, Gavin I.; Foster, Rebecca R.; Finch, Natalie
Abstract: The endothelial glycocalyx (eGlx) lines the luminal surface of endothelial cells, maintaining vascular health. Glycocalyx damage is pathophysiologically important in many diseases across species however few studies have investigated its breakdown in naturally occurring disease in dogs. The aims of the study were to investigate eGlx damage in dogs with myxomatous mitral valve disease (MMVD) diagnosed on echocardiography, and dogs in a hypercoagulable state diagnosed using thromboelastography (TEG), by measuring serum hyaluronan concentrations. Serum hyaluronan was quantified in dogs with MMVD ( n = 27), hypercoagulability ( n = 21), and in healthy controls dogs ( n = 18). Serum hyaluronan concentrations were measured using a commercially-available ELISA validated for use in dogs. Hyaluronan concentrations were compared among groups using Kruskal-Wallis tests, and post-hoc with Dunn's tests. Serum hyaluronan concentrations (median [range]) were significantly increased in dogs with MMVD (62.4 [22.8–201] ng/mL; P = 0.031) and hypercoagulability (92.40 [16.9–247.6] ng/mL; P < 0.001) compared to controls (45.7 [8.7–80.2] ng/mL). Measurement of serum hyaluronan concentration offers a clinically applicable marker of eGlx health and suggests the presence of eGlx damage in dogs with MMVD and dogs in a hypercoagulable state. Highlights: Few studies have investigated endothelial glycocalyx breakdown in disease in dogs. Serum hyaluronan is a clinically applicable marker of endothelial glycocalyx health. Serum hyaluronan was significantly increased in dogs with mitral valve disease. Serum hyaluronan was significantly increased in dogs in a hypercoagulable state. Increased serum hyaluronan may indicate glycocalyx shedding in these diseases.